2017
DOI: 10.1177/1176935117699408
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interventions of Cancers Using Intrinsically Disordered Proteins as Drug Targets: c-Myc as Model System

Abstract: The concept of protein intrinsic disorder has taken the driving seat to understand regulatory proteins in general. Reports suggest that in mammals nearly 75% of signalling proteins contain long disordered regions with greater than 30 amino acid residues. Therefore, intrinsically disordered proteins (IDPs) have been implicated in several human diseases and should be considered as potential novel drug targets. Moreover, intrinsic disorder provides a huge multifunctional capability to hub proteins such as c-Myc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 60 publications
1
26
0
Order By: Relevance
“…Disorder prediction studies show that the C-terminal region (410-490) of c-Myc is the most conserved region in protein disorder pattern and in the absence of binding partner the N-terminal region is also unstructured. Computational and experimental researches have shown that c-Myc extensively uses its disorder regions to perform diverse interactions 30 . Deregulation of the c-Myc transcription factor is involved in almost 50% of human cancers 19,30 .…”
Section: Idps In Cancer P53mentioning
confidence: 99%
See 1 more Smart Citation
“…Disorder prediction studies show that the C-terminal region (410-490) of c-Myc is the most conserved region in protein disorder pattern and in the absence of binding partner the N-terminal region is also unstructured. Computational and experimental researches have shown that c-Myc extensively uses its disorder regions to perform diverse interactions 30 . Deregulation of the c-Myc transcription factor is involved in almost 50% of human cancers 19,30 .…”
Section: Idps In Cancer P53mentioning
confidence: 99%
“…Computational and experimental researches have shown that c-Myc extensively uses its disorder regions to perform diverse interactions 30 . Deregulation of the c-Myc transcription factor is involved in almost 50% of human cancers 19,30 . A high percentage of cancer-associated proteins have long disordered regions 29 .…”
Section: Idps In Cancer P53mentioning
confidence: 99%
“…In recent studies, it is reported that several IDPs/IDPRs display disorder-toorder transitions after interaction with their partners [23]. For example, the intrinsically disordered transactivation domain of c-Myb attains an a-helical conformation after association with KIX [24][25][26][27], whereas C-terminal regulatory domain of p53 oncoprotein undergoes transitions from its disordered form into a-helical, b-structural, or two irregular forms with different configurations at binding to Cyclin A, Sirtuin, CBP, and the S100bb dimer [23,28]. To enable such folding at binding interactions with their partners, many IDPs/IDPRs are equipped with molecular recognition features (MoRFs) [29,30], which are short disorder-based binding regions that regulate the functional mechanism under physiological conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although these IDPs lack a well-folded domain structure, they have several motifs that can serve as interaction sites with other biomolecules, such as DNA, RNA, or protein [ 5 ]. Previous studies have indicated that these interactions are associated with numerous biological functions and human disorders [ 6 , 7 , 8 ]. During interactions with target proteins, IDPs, particularly IDRs, may undergo conformational changes.…”
Section: Introductionmentioning
confidence: 99%